Scaling the Moments That Matter® early childhood development model: how communities’ monitoring for change contributes to sustainable impact - Murdock, Dawn E.; Munsongo, Kelvin; Nyamor, George (Frontiers in Public Health, 2023)
This paper presents a community case study of how the Moments That Matter® (MTM) Program community-led monitoring, evaluation and learning (MEL) system contributes a scalable model with quality and sustainable impact. With a faith-based approach, MTM is an early childhood development program partnership of Episcopal Relief & Development which is rooted in parenting empowerment and community ownership. MTM empowers Primary Caregivers, strengthening nurturing care of some sixty thousand children aged under three since 2012. Launched in Zambia, MTM has expanded to five other countries. Based on MTM Zambia and Kenya, this paper examines how an innovative, community-led MEL system functions to drive sustainable impacts and scaling. Measurement for change has been critical to the community MEL system. MTM is people-centered with community leaders, ECD service providers, volunteers and Primary Caregivers all setting their specific goals. The program is inclusive with all stakeholders engaged in monitoring and making adjustments; interactive with relationship-based social and behavior change strategies; informative with continuous data gathering used for decisions and problem-solving; and dynamic with built-in flexibility and an adaptation process. The community-led MEL propels scaling up through two channels: 1. New Communities for MTM Program Start Up: As MTM communities graduate to community ownership, program staff and budget are then invested in new marginalized and underserved rural areas. 2. Deepening Reach within MTM Communities: Over the first two cycles, communities transition to community ownership, then continue independently of staff and budget. They identify a new set of vulnerable Primary Caregivers of children under three and carry out the caregiver parenting support and learning activities. The success of the program’s community-led MEL in achieving sustainable change and fueling the program scale up hinges on three factors: 1. Initiating the community-led MEL dimension at project start, gradually increasing the community role while reducing the staff role. 2. Provision of Community MEL capacity-building and effective, user-friendly tools to be tailored locally. 3. Three program stakeholder types leading MEL and collaborating closely with each other: ECD Committees with MTM-trained faith leaders, ECD Promoters, and Primary Caregivers of children under three.